Redescription and generic placement of Neopamera mumfordi (Van Duzee, 1935) and Remaudiereana castanea (Van Duzee, 1935) (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae) - Dellapé, Pablo M.; Malipatil, M. B. (Zootaxa, 2012)
A new genus, Neocnemodus gen. nov., is erected to accommodate Neopamera mumfordi (Van Duzee) from the Marquesas Islands; the species is redescribed and illustrated, and its relationships with the genera Cnemodus Herrich-Schaeffer and Andercnemodus Brailovsky & Cervantes-Peredo are analysed. Another Marquesas Island myodochine species, Remaudiereana castanea (Van Duzee), is redescribed, illustrated, and its generic placement discussed.